The Emerald International Handbook of Technology-Facilitated Violence and Abuse 2021
DOI: 10.1108/978-1-83982-848-520211002
|View full text |Cite
|
Sign up to set email alerts
|

Is it Actually Violence? Framing Technology-Facilitated Abuse as Violence

Abstract: When discussing the term "Technology-Facilitated violence" (TFV) it is often asked: "Is it actually violence?" While international human rights standards, such as the United Nations' Convention on the Elimination of All Forms of Discrimination against Women (United Nations General Assembly, 1979), have long recognized emotional and psychological abuse as forms of violence, including many forms of Technology-Facilitated abuse (United Nations, 2018), law makers and the general public continue to grapple with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The scarcity of results on this topic indicates that violence in the offline is more easily detected than that occurring in the online world (Sánchez-Hernández et al, 2020). This may be due to misinterpretation by observers, who consider that these online behaviors are less harmful to the victims (Dunn, 2020), and therefore tend to go unnoticed. Another explanation could be overexposure to gender-based cyberviolence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scarcity of results on this topic indicates that violence in the offline is more easily detected than that occurring in the online world (Sánchez-Hernández et al, 2020). This may be due to misinterpretation by observers, who consider that these online behaviors are less harmful to the victims (Dunn, 2020), and therefore tend to go unnoticed. Another explanation could be overexposure to gender-based cyberviolence.…”
Section: Discussionmentioning
confidence: 99%
“…Several forms of gender-based violence perpetrated on social networks are still not viewed as forms of violence by the wider public. Online abuse is minimized because of the mistaken belief that it is not as harmful as abuse occurring in the offline world (Dunn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This action is carried out using the internet and/or mobile technology that harms others based on their sexual or gender identity or by enforcing harmful gender norms' (Hinson et al, 2019). Technologyfacilitated GBV includes cyberstalking, cyberbullying, sexual harassment, image-based abuse, doxing and impersonation (Backe et al, 2018;Hinson et al, 2018;Dunn, 2020;Henry et al, 2020). Global prevalence of witnessing or experiencing technologyfacilitated GBV for women and girls has been found to be as high as 85 per cent, with some reports showing prevalence in Asia to be as high as 88 per cent (EIU, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Like offline GBV, the risk of experiencing technology-facilitated violence seems to vary by individuals' gender, sexual orientation, caste, religion, nationality and economic status, among other identity aspects. In addition to demographic characteristics, the anonymity and unknown proximity of perpetrators are unique factors that promote harassment and make it difficult to determine or prosecute the perpetrator (Duggan et al, 2014;Henry and Powell, 2015;Hinson et al, 2019;Afrouz, 2021;Dunn, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Internet has been proven to be the perfect medium for it (Suzor et al 2019 ). One study has attempted to operationalize OGBV based on the most frequently reported acts which include unwanted messages, harassment, exposure to unwanted explicit materials, doxxing, and even sexual threats or exploitation (Vitak et al 2017 ; Dunn 2020 ).…”
Section: Introductionmentioning
confidence: 99%